Pengaruh Penambahan Ekstrak Daun Stevia ( Stevia rebaudiana (Bertoni)) terhadap Daya Terima, Kandungan Gizi, dan Aktifitas Antioksidan Kefir Susu Kambing - Angga Hardiansyah; Hesti Arum Halimah; Widiastuti Widiastuti (Universitas Islam Negeri Walisongo Semarang, 2022)
The purpose of this study was to determine the effect of adding stevia leaf extract to the acceptability test, nutritional quality content, and antioxidant activity content of goat milk kefir. This research method used an experimental method with a completely randomized design with four treatments and two repetitions. Treat P0, namely 0% control, 5% P1, 10% P2, and 15% P3, with the addition of stevia leaf extract. The modified sample was tested on 30 untrained panelists. Data analysis for organoleptic tests used the Kruskall-Wallis analysis method, and if there were significant differences, it was continued with the Mann-Whitney test. Laboratory test analysis data is used using the independent sample t test analysis method to determine the difference between the selected formula and the control. Acceptability test results on the aspect of preference (overall) showed that the most preferred formula was P3 (15% addition of stevia leaf extract) with an average value of 4.00 (P=0.001). Statistical test results for differences in control formula (P0) and selected formula (P3) on water content (P=0.051), ash content (P=0.301), fat content (P=0.010), protein content (P=0.029), sugar content total (P=0.025) and antioxidant activity (P=0.001). The addition of stevia leaf extract increased the acceptability and antioxidant activity of goat's milk kefir.Â Tujuan penelitian ini adalah mengetahui pengaruh penambahan ekstrak daun stevia terhadap daya terima, kandungan gizi, dan aktivitas antioksidan kefir susu kambing. Penelitian ini menggunakan desain eksperimental menggunakan rancangan acak lengkap dengan empat perlakukan dan dua kali pengulangan. Perlakukan P0 yaitu 0% kontrol, P1 dengan 5% penambahan ekstrak daun stevia, P2 10% dan P3 15%. Produk diujikan pada 30 panelis tidak terlatih. Hasil organoleptik diuji menggunakan uji Kruskall Wallis dan uji Mann-Whitney. Uji laboratorium menggunakan metode analisis Independent sample t test untuk mengetahui perbedaan antarformula. Hasil uji daya terima pada aspek kesukaan (overall) menunjukkan formula paling disukai yaitu P3 (15% daun stevia ) dengan nilai rata-rata 4,00 (P=0,001). Hasil uji statistik perbedaan formula kontrol (P0) dan formula terpilih (P3) pada kadar air (P=0,051), kadar abu (P=0,301), kadar lemak (P=0,010), kadar protein (P=0,029), kadar gula total (P=0,025) dan aktivitas antioksidan (P=0,001). Penambahan ekstrak daun stevia meningkatkan daya terima dan aktivitas antioksidan kefir susu kambing.